Incubation period and risk factors support sexual transmission of bacterial vaginosis in women who have sex with women. (14th March 2019) - Muzny, Christina Ann; Lensing, Shelly Y; Aaron, Kristal J; Schwebke, Jane R
Abstract : Objective: The epidemiology of bacterial vaginosis (BV) favours sexual transmission of BV-associated bacteria. We examined incubation period and risk factors for incident BV (iBV) in a prospective study of women who have sex with women (WSW). Methods: Using daily self-collected vaginal swabs, WSW with normal vaginal microbiota (no Amsel criteria and a Nugent score of 0–3) were followed for 90 days or until iBV (Nugent score 7–10 on at least 2–3 consecutive days). Daily diaries of sexual activity and menses were completed. Time to iBV was estimated. Accounting for differing lengths of follow-up and age, rates of sexual activities (per 100 person-days (pd)) were compared according to iBV status. The relationship between menses and iBV was also investigated. Results: Of the 36 WSW, the mean age was 30 years (SD 8) and 92% were African American. The probability of iBV at 30 and 60 days was 20% (SD 7%) and 36% (SD 8%), respectively; 14 (39%) developed iBV by 90 days. In WSW with iBV versus those without iBV, the relative rate of any sexual activity prior to iBV was 40% higher (20.4 vs 14.6 per 100 pd; p=0.010), sex with a woman was 38% higher (14.3 vs 10.3 per 100 pd; p=0.038), digital-vaginal sex was 57% higher (14.3 vs 9.1 per 100 pd; p=0.005) and digital-anal sex was 5.6 times higher (2.9 vs 0.5 per 100 pd; p<0.001). iBV was more likely for those WSW with menses in the prior 2 days as compared with those without recent menses (HR 3.4; p=0.029). Sexual activity occurred in 93% WSW at a median of 4 days (95% CI 2 to 6) prior to iBV. Conclusion: iBV was common and associated with sexual activity in this cohort of predominantly African American WSW. An incubation period of 4 days is consistent with other bacterial STIs.